Islam in the world - Ruthven, Malise (Oxford University Press, 2006)
This invaluable introductory guide provides a complete and lively summary of Islam, one of the most worldly of the great religions, in which the quest for spiritual fulfillment is inevitably bound up with political aspirations. Malise Ruthven presents a full overview of the religion in its historical, geographic, and social settings.